2022
DOI: 10.4103/aian.aian_1138_21
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Headache Disorders

Abstract: Air pollution, the most prevalent form of pollution worldwide, is associated with a wide range of neurological disorders, including neurodegenerative conditions, stroke, autism, depression, and developmental delay. There is accumulating evidence on the association between air pollution and headache disorders, especially migraine. Many classical and non-classical air pollutants have been associated with headache, including particulate matter, nitrogen dioxide, sulfur dioxide, ozone, carbon monoxide, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Two recent publications have briefly reviewed associations between air pollution and headache and/or migraine 13,55 . The overall conclusions of these papers are in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Two recent publications have briefly reviewed associations between air pollution and headache and/or migraine 13,55 . The overall conclusions of these papers are in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…4,6,9 Two recent publications have briefly reviewed associations between air pollution and headache and/or migraine. 13,55 The overall conclusions of these papers are in agreement with our results. A scoping review that included a summary of air pollution and headache 55 reported point estimates above the null value for associations between migraine outcomes and carbon monoxide, nitrogen dioxide, ozone, PM 2.5 , and PM 10 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Data on long-term exposures in relation to migraine are very scarce. However, they suggest that chronic exposure may be important in the etiopathogenesis of migraine ( 38 ).…”
Section: Discussionmentioning
confidence: 99%